Transcriptomic and Proteomic Profiling Revealed High Proportions of Odorant Binding and Antimicrobial Defense Proteins in Olfactory Tissues of the House Mouse - Kuntová, Barbora; Stopková, Romana; Stopka, Pavel (Frontiers in Genetics, 2018)
Mammalian olfaction depends on chemosensory neurons of the main olfactory epithelia (MOE), and/or of the accessory olfactory epithelia in the vomeronasal organ (VNO). Thus, we have generated the VNO and MOE transcriptomes and the nasal cavity proteome of the house mouse, Mus musculus musculus. Both transcriptomes had low levels of sexual dimorphisms, whilst the soluble proteome of the nasal cavity revealed high levels of sexual dimorphism similar to that previously reported in tears and saliva. Due to low levels of sexual dimorphism in the olfactory receptors in MOE and VNO, the sex-specific sensing seems less likely to be dependent on receptor repertoires. However, olfaction may also depend on a continuous removal of background compounds from the sites of detection. Odorant binding proteins (OBPs) are thought to be involved in this process and in our study Obp transcripts were most expressed along other lipocalins (e.g. Lcn13, Lcn14) and antimicrobial proteins. At the level of proteome, OBPs were highly abundant with only few being sexually dimorphic. We have, however, detected the major urinary proteins MUP4 and MUP5 in males and females and the male-biased central/group-B MUPs that were thought to be abundant mainly in the urine. The exocrine gland-secreted peptides ESP1 and ESP22 were male-biased but not male-specific in the nose. For the first time, we demonstrate that the expression of nasal lipocalins correlates with antimicrobial proteins thus suggesting that their individual variation may be linked to evolvable mechanisms that regulate natural microbiota and pathogens that regularly enter the body along the ‘eyes-nose-oral cavity’ axis.